Identifikasi Kerusakan Shaft Roda Gigi Pompa Oli Diesel Engine Dengan Menggunakan Metode Fault Tree Analysis - Wilarso Wilarso; Wisnu Pracoyo (Rekayasa Material, Manufaktur dan Energi, 2019)
A damage to the oil pump drive shaft on one of the generator sets PT.X. Failure begins with an indication of a decrease in oil pressure where the oil pressure indicator points to the number 0 (zero). Based on the electronic control module (ECM) download data, it was noted that the unit had experienced 4 times low oil pressure warning and 4 times low oil pressure shutdown. During visual checking, the crankshaft suddenly stops spinning (jammed). To identify the initial damage associated with low oil pressure and the crankshaft stops rotating (crankshaft jammed), an oil pump component is dismantled. In a visual inspection found broken oil pump drive gear. In identifying oil pump failure and analysis using the Fault Tree Analysis method. Based on the FTA the oil pump failure is caused by 4 (four) factors including, 1. Oil quality, 2. Contamination control, 3, Material quality, and 4. Maintenance, from the four causes which are the main causes of control contamination, due to the presence of material metal above the axle goes to the oil pump. Based on the initial material test the broken gear begins with the outer circle and the final fracture in the center of the gear shaft, from the microstructure testing of the fracture shape there is no beachmark on the broken surface and the final shape of the rough fracture, that the gear shaft is broken in a short time.